Effects of Carbon Doping and Annealing Temperature on Magnetic MnAl Powders and MnAl Polymeric Composites - Wannisa Thongsamrit; Thanida Charoensuk; Panissa Saetang; Pongsakorn Jantaratana; Chesta Ruttanapun; Chitnarong Sirisathitkul (My University, 2021)
Process parameters leading to magnetic polymer composites, an essential ingredient in the additive manufacturing of rare-earth-free magnets, are investigated. The induction melting of manganese (Mn) and aluminum (Al), and subsequent annealing at 450, 500, or 550 °C for 20 min, gave rise to ferromagnetic τ–MnAl phase, as well as other phases. The nonmagnetic Al4C3 and oxide phases were then removed by the magnetic separation. Magnetic powders from the magnetic separation were incorporated in polylactic acid (PLA) matrix via a solution route. The remanent magnetization as high as 4.3 emu/g in the powder form was reduced to 2.3–2.6 emu/g in the composites. The reduction in coercivity was minimal, and the largest value of 814 Oe was obtained when the powder annealed at 450 °C was loaded in the composite. The phase composition and hence magnetic properties were even more sensitive to the carbon (C) doping. Interestingly, the addition of 3% C led to coercivity as high as 1445 Oe in MnAl–C powders without further annealing. The enhanced coercivity was attributed to the domain wall pinning by the AlMn3C phase, and magnetizations are likely increased by this phase.
Keywords: Magnetic Properties of Alloys